Financial management at Danmarks nationalbank - Danmarks nationalbank (Copenhagen : Danmarks nationalbank, 2003)
Provides a full description of Danmarks nationalbanks's portofolio management and financial management.
Includes bibliographical references.
oif 06/03/15
Loan
Keywords: Danmarks nationalbank -- Finance; Banks and banking, Central -- Denmark -- Finance